Implementasi Kurikulum Merdeka dalam Pembelajaran Bahasa Indonesia di SMP - Oktaviyanti, Nur'aini; Andayani, Andayani (Ikaprobsi, 2023)
This research is a qualitative descriptive study with a case study approach. The sampling technique was carried out by purposive sampling. Data collection was carried out using passive participatory observation techniques, document analysis, interviews, and questionnaires. The data validity test technique uses the data source triangulation method. The results of the study found that the procedures carried out by the teacher in carrying out lesson planning were different from the suggestions given by the government. The teacher carries out the lesson plan with the stages of (a) analysis of learning outcomes that can be used to develop objectives and flow of learning objectives, (b) developing teaching modules, (c) adjusting learning outcomes to the stages of achievement and characteristics of students, (d) conducting learning evaluations and assessment. Second, the implementation of Indonesian language learning is not in accordance with the teaching modules that have been planned by the teacher starting from the learning activity steps, learning methods, learning media and assessment assessments that have been planned. Third, learning planning has obstacles in the process of adapting to the use of an independent curriculum, difficulties in using the Free Teaching Platform (PMM) application in understanding an independent curriculum, teachers have difficulty managing time, an independent curriculum assessment system, alignment of material in teaching modules, and completeness of student books. Then, there are obstacles in the implementation of learning, namely students are still adapting from distance learning to face-to-face learning and the teacher lacks control over the situation in class conditions. Penelitian ini merupakan penelitian deskriptif kualitatif dengan pendekatan studi kasus. Teknik pengambilan sampel dilakukan dengan purposive sampling. Pengumpulan data dilakukan dengan teknik observasi partisipasi pasif, analisis dokumen, wawancara, dan penyebaran angket. Teknik uji validitas data menggunakan metode triangulasi sumber data. Hasil penelitian menemukan bahwa prosedur yang dilaksanakan guru dalam melakukan perencanan pembelajaran berbeda dengan saran yang diberikan pemerintah. Guru melaksanakan perencanaan pembelajaran dengan tahapan (a) analisis capaian pembelajaran yang dapat digunakan untuk menyusun tujuan dan alur tujuan pembelajaran, (b) mengembangkan modul ajar, (c) menyesuaikan capaian pembelajaran dengan tahap capaian dan karakteristik peserta didik, (d) melakukan evaluasi pembelajaran dan asesmen. Kedua, pelaksanaan pembelajaran Bahasa Indonesia belum sesuai dengan modul ajar yang telah direncanakan oleh guru mulai dari langkah kegiatan pembelajaran, metode pembelajaran, media pembelajaran dan penilaian asesmen yang telah direncanakan. Ketiga, perencanaan pembelajaran memiliki hambatan pada proses adaptasi penggunaan kurikulum merdeka, kesulitan dalam penggunaan aplikasi Platform Merdeka Mengajar (PMM) dalam pemahaman kurikulum merdeka, guru kesulitan memanajemen waktu, sistem penilaian kurikulum merdeka, penyelarasan materi dalam modul ajar, dan kelengkapan buku siswa. Kemudian, hambatan dalam pelaksanaan pembelajaran, yakni siswa masih beradaptasi dari pembelajaran jarak jauh menjadi pembelajaran tatap muka dan guru kurang menguasai situasi kondisi kelas.